2020
DOI: 10.3390/s20113176
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Platinum Electrodes for Dry Ear-EEG Measurements

Abstract: The interest in dry electroencephalography (EEG) electrodes has increased in recent years, especially as everyday suitability earplugs for measuring drowsiness or focus of auditory attention. However, the challenge is still the need for a good electrode material, which is reliable and can be easily processed for highly personalized applications. Laser processing, as used here, is a fast and very precise method to produce personalized electrode configurations that meet the high requirements of in-ear EEG electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In order to solve these problems, methods to increase the effective surface area while reducing the geometrical dimension of the entire electrode have been proposed. Surface roughening techniques by utilizing nanoporous platinum, platinum black electro-patterning, Ag-TiN coating, and nano-patterning based on pillar or arch shapes are developed to measure EEG precisely when using extreme small electrodes [ 36 38 ]. Such electrodes are actively manufactured in various bio-potential measurement fields and are expected to get more increasing interest in wearable ultra-small EEG measurement.…”
Section: Miniaturization Techniques For Eeg Recording Hardwarementioning
confidence: 99%
“…In order to solve these problems, methods to increase the effective surface area while reducing the geometrical dimension of the entire electrode have been proposed. Surface roughening techniques by utilizing nanoporous platinum, platinum black electro-patterning, Ag-TiN coating, and nano-patterning based on pillar or arch shapes are developed to measure EEG precisely when using extreme small electrodes [ 36 38 ]. Such electrodes are actively manufactured in various bio-potential measurement fields and are expected to get more increasing interest in wearable ultra-small EEG measurement.…”
Section: Miniaturization Techniques For Eeg Recording Hardwarementioning
confidence: 99%
“…Although there are some drawbacks such as a limited number of electrodes and reduced signal amplitude, several works have demonstrated its feasibility as a facile and unobtrusive neural interface ( Figure 4 B) ( Hoon Lee et al., 2014 ; Kidmose et al., 2013 ; Lee et al., 2018a ). Moreover, it was also demonstrated that the signal quality of this dry electrode was comparable to the conventional EEG system using conductive gels owing to the close contact between the devices and sweat/hair-free surfaces ( Eickenscheidt et al., 2020 ; Kappel et al., 2019 ; Looney et al., 2012 ).…”
Section: Advances In Neural Device Platformsmentioning
confidence: 78%
“…Without the requirements of skin preparation and conducting gel, this electrode can provide a lower and stable surface impedance, which is suitable for long-term EEG measurements (Figure c). Eickenscheidt et al reported a highly porous flexible platinum electrode fabricated via fast laser-aided manufacturing process and electrodeposition (Figure d) . As a flexible electrode, the porous platinum showed good properties, especially in the relevant frequency range from 0.1 to 500 Hz, illuminating a potential application possibility for in-ear EEG (Figure e).…”
Section: Electrode Technologies For Noninvasive Bcimentioning
confidence: 99%